2020
DOI: 10.1038/s41467-020-17566-x
|View full text |Cite
|
Sign up to set email alerts
|

Néel-type skyrmion in WTe2/Fe3GeTe2 van der Waals heterostructure

Abstract: The promise of high-density and low-energy-consumption devices motivates the search for layered structures that stabilize chiral spin textures such as topologically protected skyrmions. At the same time, recently discovered long-range intrinsic magnetic orders in the two-dimensional van der Waals materials provide a new platform for the discovery of novel physics and effects. Here we demonstrate the Dzyaloshinskii-Moriya interaction and Néeltype skyrmions are induced at the WTe 2 /Fe 3 GeTe 2 interface. Transp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
234
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(243 citation statements)
references
References 37 publications
9
234
0
Order By: Relevance
“…Once established, by taking advantages of other 2D crystals that are stackable and offer unique electrical properties [1,2], this material platform could provide a different route towards skyrmion-based devices that have been challenging with conventional metallic ferromagnets [20,21]. Recently, skyrmionlike spin textures have been observed experimentally in exfoliated vdW ferromagnet materials (e.g., FGT and Cr 2 Ge 2 Te 6 ) and their heterostructures with the magnetic fields [22][23][24][25][26]. However, both Bloch-type and Néel-type skyrmions of the previous results have still been a subject of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Once established, by taking advantages of other 2D crystals that are stackable and offer unique electrical properties [1,2], this material platform could provide a different route towards skyrmion-based devices that have been challenging with conventional metallic ferromagnets [20,21]. Recently, skyrmionlike spin textures have been observed experimentally in exfoliated vdW ferromagnet materials (e.g., FGT and Cr 2 Ge 2 Te 6 ) and their heterostructures with the magnetic fields [22][23][24][25][26]. However, both Bloch-type and Néel-type skyrmions of the previous results have still been a subject of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many significant results, these methods have limited spatial resolution due to the laser diffraction limit and electrode size. The nanoscale features of the atomically thin vdW magnets, such as magnetic domains [15][16][17] and topological spin textures [18][19][20][21] , are largely unexplored. For example, magnetic domains in layered CrBr 3 have been predicted from its anomalous hysteresis loop in magneto-photoluminescence and micromagnetometry measurements 15,16 , but the magnetic domain structure and its evolution has not been detected in real space.…”
mentioning
confidence: 99%
“…Using criticality analysis, Tan et al [20] have demonstrated that the coupling length between vdW layers in Fe 3 GeTe 2 is estimated to be 5 layers. Wu et al [45] have confirmed that the increasing of the thickness of FGT up to 4-60 layers will lead to greatly enhanced DM interaction. In short, we have demonstrated that the strong SOC in the In 2 Se 3 layers does induce an interfacial DM interaction at the interface with FGT, and have achieved the robust manipulation of DM interaction in the Fe 3 GeTe 2 /In 2 Se 3 heterostructure.…”
Section: Resultsmentioning
confidence: 93%
“…To validate the plausible mechanism of ferroelectricallydriven DM interaction, we performed first-principles calculation on the FGT/In 2 Se 3 HS (see Supplementary Information for may be result of the broken inversion symmetry and the strong SOC effect [45,46]. Our FGT/In 2 Se 3 HS has the polarizationdependent DM interaction, which can be used in skyrmionbased racetrack memory.…”
Section: Resultsmentioning
confidence: 99%